Environmental impact assessment to support the development of new Photonic Meta-Concrete. Issue 1 (1st September 2022) - Adams, N; Allacker, K
Abstract: The cooling demand in buildings has increased over the past decades due to global warming, the heat-island-effect in cities and the increased airtightness and thermal resistance of the building envelope. This led to an increased use of conventional air-conditioners, which now account for 7% of global greenhouse gas emissions and 10% of the total energy consumption. In this context, the MIRACLE project aims at developing a new Photonic Meta-Concrete (PMC) with remarkable photonic properties to reduce the CO2 footprint of buildings, mitigate the heat-island-effect and global warming. Besides the positive effect that this innovative material can have on the environment during the use phase of buildings, also the environmental impact of the production needs to be minimized. Environmental impact assessment (EIA) is used along the development process of this innovative material to guarantee a low material environmental impact. This paper discusses how EIA is used along the development process and presents the preliminary results in the early stages of the development of the PMC. To investigate the impact of this new material, a cradle-to-gate analysis of the resources, energy and machinery needed to create the concrete mixture is performed. The broad set of environmental indicators of the EC PEF (Product Environmental Footprint) method, such as climate change, acidification, eutrophication, particulate matter, ecotoxicity, water depletion and human toxicity are being considered. Considering such a large set of indications ensures that burden shifting is avoided. The environmental impact of the PMC is moreover compared to the impact of conventional concrete to understand how both perform.